Land and agrarian reform in Zimbabwe : beyond white-settler capitalism - Moyo, Sam; Chambati, Walter (Codesria book series., 2013)
"This book comes to a conclusion that the Zimbabwe land reform represents a new form of resistance with distinct and innovative characteristics when compared to other cases of radicalisation, reform and resistance. The process of reform and resistance has entailed the deliberate creation of a tri-modal agrarian structure to accommodate and balance the interests of various domestic classes, the progressive restructuring of labour relations and agrarian markets, the continuing pressures for radical reforms (through the indigenisation of mining and other sectors), and the rise of extensive, albeit relatively weak, producer cooperative structures. The book also highlights some of the resonances between the Zimbabwean land struggles and those on the continent, as well as in the South in general, arguing that there are some convergences and divergences worthy of intellectual attention. The book thus calls for greater endogenous empirical research which overcomes the pre-occupation with failed interpretations of the nature of the state and agency in Africa."--Publisher's website.